Protective Effects and Possible Mechanisms of Actions of Bushen Cuyun Recipe on Diminished Ovarian Reserve Induced by Cyclophosphamide in Rats - Jiang, Mei; Wang, Weiling; Zhang, Jingxuan; Wang, Chunguo; Bi, Yucong; Li, Pin; Yang, Song; Li, Jialin; Xu, Yan-Tong; Wang, Ting (Frontiers in Pharmacology, 2020)
Backgrounds: Diminished ovarian reserve (DOR) contributes significantly to female subfertility. Bushen Cuyun Recipe (BCR, Tradename Yueliang Yin), a marketed product in China, showed potent effects in treatment of female subfertility in clinical practices of traditional Chinese medicine (TCM). In this study, we aimed to investigate chemical compositions, efficacy in scientific evidences and pharmacological mechanisms of BCR in DOR treatments. Methods: Chemical compositions of BCR were determined by UHPLC-LTQ-Orbitrap MS method. DOR model in rats were induced by intraperitoneal injection of cyclophosphamide (CTX) 90mg/kg once. After CTX treatment for14 days, rats were administrated intragastrically with deionized water, dehydroepiandrosterone (DHEA) or BCR in low, middle and high dose for 30 days. Ovarian index, ovarian morphology, follicle number, and anti-Müllerian hormone (AMH) in serum were determined to assess effects of BCR. To investigate possible mechanisms, network pharmacological analysis was used to predict possible pathways in BCR effects on female infertility. In experimental studies, contents of hormones in hypothalamic-pituitary-ovarian axis (HPOA, including estradiol (E2), follicle-stimulating hormone (FSH) and gonadotropin releasing hormone (GnRH)) and pyroptosis related protein, including gasdermin D (GSDMD), caspase-1 and interleukin-18 (IL-18) in ovarian were detected by ELISA, immunofluorescence and Western blot. Results: Our results show that following treatment with BCR in DOR rats, several measures showed significant improvement. The morphology of ovary, ovarian index, estrous cycle, growing follicles and corpus luteum from latest ovulation, and serum AMH recovered to approximately normal levels. Furthermore, network pharmacological analysis suggested that NOD-like receptor signaling pathway ranked as the most important one in BCR mechanisms in female infertility. Experimental results of action mechanisms revealed that content of DOR rats serum FSH was decreased and contents of serum GnRH and E2 were elevated after BCR treatments, suggesting the role of BCR on HPOA. And the elevated level of GSDMD, caspase-1 and IL-18 was reversed in BCR treated rats. Conclusions: Chemical compositions of BCR were first identified in present study. BCR was demonstrated to show potent protective effects on DOR. The possible mechanisms of BCR on the DOR might mediate by regulating gonadal hormones of HPOA and protecting granulosa cells in ovary against pyroptosis.